Powojenne granice. Polityka brytyjskiego rządu w kształtowaniu mapy Europy w latach 1918–1921 - Jeziorny, Dariusz (1968– ) (Instytut Historii PAN, 2024)
As a global power, Britain played a crucial role in establishing new borders after the First World War. David Lloyd George’s cabinet was instrumental in shaping the new order during the Peace Conference and in subsequent agreements, such as the Treaty of Riga. This article explores the British mindset and priorities regarding border delimitation, focusing on both borders of significant strategic importance to London and those that held no direct relevance to British interests.
p. 135-154
Summary in English.
Keywords: Great Britain; border demarcation; world war; World War (1914-1918) - territorial questions; Great Britain - foreign relations - 1910-1936; Paris Peace Conference (1919/1920); Treaty of Riga (1921); Lloyd George, David (1863-1945)